Effects of disturbance on marginal populations: Human trampling on Ascophyllum nodosum assemblages at its southern distribution limit - Araújo, R. (2014)
The negative effects of disturbances on the long-term persistence of populations may be more severe in marginal populations, i.e. those occurring at the boundaries of geographical and eco- logical distribution ranges. Human trampling is an important source of anthropogenic disturbance for intertidal assemblages. Effects of human trampling on intertidal rocky shore assemblages dominated by Ascophyllum nodosum (L.) Le Jol. at its southern distributional limit in Europe were tested exper- imentally. Four different intensities of trampling disturbances were applied to experimental areas, over a period of 5 mo. Percentage cover of A. nodosum and associated organisms was quantified dur- ing the disturbance period and for a recovery period of 1 yr. The 2 highest trampling intensities dras- tically reduced the cover of A. nodosum. Trampling also negatively affected Fucus vesiculosus and understorey species, while indirectly allowing colonisation by ephemeral green algae. One year after the end of disturbance, A. nodosum assemblages in the highest disturbance intensity areas were still significantly different from assemblages in the control and lowest disturbance intensity areas. These results were mainly driven by a switch in the dominant canopy species, from A. nodosum to F. vesicu- losus. Results obtained in this study show that disturbance by human trampling negatively affects A. nodosum assemblages and that the effects are dependent on trampling intensity. These findings highlight the risk of local extinction imposed on these populations by anthropogenic disturbance, and the consequent need for protection measures for such sensitive populations.